2018
DOI: 10.1016/j.phymed.2018.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mycobacterium tuberculosis activity of essential oil and 6,7-dehydroroyleanone isolated from leaves of Tetradenia riparia (Hochst.) Codd (Lamiaceae)

Abstract: These results revealed that TrEO isolated from leaves of T. riparia and the pure compound 6,7-dehydroroyleanone display good activity against M. tuberculosis clinical isolates, including MDR isolates, with low cytotoxicity to murine macrophages. The 6,7-dehydroroyleanone compound is a potential candidate for anti-TB drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…Concerning chemical constituents, some terpenes have already had their antimycobacterial activity evaluated. Isoprenes, such as monoterpenes, sesquiterpenes and related alcohols and phenols, have been responsible for antimycobacterial activity of EOs (Baldin et al 2018). It should be emphasized that the promising antitubercular activity of EOs from S. odoratissima may be attributed to β-caryophyllene, a terpene whose favorable biological activity has already been described in the literature, mainly its antioxidant, antitumor and antimicrobial properties (Dahham et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Concerning chemical constituents, some terpenes have already had their antimycobacterial activity evaluated. Isoprenes, such as monoterpenes, sesquiterpenes and related alcohols and phenols, have been responsible for antimycobacterial activity of EOs (Baldin et al 2018). It should be emphasized that the promising antitubercular activity of EOs from S. odoratissima may be attributed to β-caryophyllene, a terpene whose favorable biological activity has already been described in the literature, mainly its antioxidant, antitumor and antimicrobial properties (Dahham et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The HMBC spectrum allowed us to place the chlorinated side chain and the rearranged methyl group at the correct positions by selected Leishmanicidal activity of (2) and 3Recently, activity against Mycobacterium tuberculosis, Leishmania amazonensis, Staphylococcus aureus and Caenorrhabditis elegans was demonstrated for the essential oil from T. riparia and some of its isolated constituents. 3,[14][15][16][17] Here, we evaluated the activity of 7α-hydroxyroyleanone (1), extracted from T. riparia leaves and the product of its dehydration reaction (2), against Leishmania amazonensis, a parasite that can cause different clinical disease manifestations such as cutaneous leishmaniasis, which may evolve to the severe anergic diffuse cutaneous disease, and the visceral leishmaniasis as well. [18][19][20][21] Our results demonstrated that the diterpenequinone (1) exhibits a dose dependent anti-Leishmania promastigote activity with half maximal inhibitory concentration (IC 50 ) of 2.96 μg mL -1 ( Table 2).…”
Section: Structural Identification Of (2)mentioning
confidence: 99%
“…2 The plant is used as a remedy against a wide range of diseases including malaria, angina, gastroenteritis, diarrhea, influenza, respiratory problems and symptoms such as headaches, fever, stomachaches, etc. 3,4 Studies have shown that extracts of leaves of T. riparia as well as its essential oil exhibited antimicrobial activities against bacteria and fungi such as Mycobacterium tuberculosis, M. smegmatis, M. simiae, Staphylococcus aureus and Candida albicans. 3 The diterpenequinone 7α-hydroxyroyleanone, also known as horminone, 5 was shown to be one of the active compounds against tuberculosis (TB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent investigation demonstrated that essential oil isolated from leaves of Tetradenia riparia and the pure compound 6,7-dehydroroyleanone display good activity against Mycobacterium tuberculosis clinical isolates, including MDR isolates, with low cytotoxicity to murine macrophages. The 6,7-dehydroroyleanone compound is a potential candidate for anti-TB drug (BALDIN et al, 2018).…”
Section: Natural Products From Aromatic and Medical Plants As Antimicmentioning
confidence: 99%